Нелинейная схема компромиссов в многокритериальных задачах оценивания и оптимизации - Воронин, А.Н. (Кибернетика и системный анализ, 2009)
Викладено концепцію нелінійної схеми компромісів у багатокритеріальних задачах оцінювання й оптимізації. Показано, що проблема полягає в коректній апроксимації функції корисності і побудові адекватної даної ситуації змістовної математичної моделі (скалярної згортки) для рішення різних багатокритеріальних задач. У задачі аналізу ця згортка має сенс цільової функції. В результаті її екстремізації отримується компромісно-оптимальний вектор аргументів. Наведено модельний приклад. The concept of a nonlinear trade-off scheme in multicriteria problems of evaluation and optimization is presented. It is shown that the problem is to approximate correctly the utility function and construct substantial mathematical model (scalar convolution) adequate to the given situation to solve various multicriteria problems. In analysis problems, this convolution is an estimator, its value expresses quantitatively the measure of quality of a multicriteria object for preset values of arguments. In optimization problems, of the scalar convolution has a meaning of the objective function. An illustrative example is given.